GERAKAN ISLAM TRANSNASIONAL DAN PERUBAHAN PETA DAKWAH DI INDONESIA - Syaoki, Muhammad (Universitas Islam Negeri Mataram, 2017)
A variety of circumstances that occur in the Islamic world sparked the birth of such transnational Islamic movement Hizbut Tahrir, Talbligh, and the Ahmadiyya Jamaat. The transnational nature of the Islamic movement of expansiveness and actively spreading their thinking about Islam belongs to Indonesia. As a country that is the world’s largest Muslim population, Indonesia became fertile ground for the development of transnational Islamic movement. This condition could have made the bases of moderate Islam, which has developed in Indonesia threatened his position. For that it needs the presence of map propagation, especially in Indonesia as the reference design strategy of da’wah that would be used in order to perform filtering and prevent the occurrence of friction with transnational Islamic movement. Therefore, the charity should also be adjusted to the pace of the times, a da’i sued for control of not only the sciences of religion, but also in science and technology. Is thereby expected later a da’i can offset the influence of transnational Islamic movement in Indonesia.